2015
DOI: 10.3325/cmj.2015.56.246
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic vs natural scaffolds for human limbal stem cells

Abstract: AimTo investigate the impact of synthetic electrospun polyurethane (PU) and polycaprolactone (PCL) nanoscaffolds, before and after hydrolytic surface modification, on viability and differentiation of cultured human eye epithelial cells, in comparison with natural scaffolds: fibrin and human amniotic membrane.MethodsHuman placenta was taken at elective cesarean delivery. Fibrin scaffolds were prepared from commercial fibrin glue kits. Nanoscaffolds were fabricated by electrospinning. Limbal cells were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The variation in the response of the micro TiO 2 based scaffolds, is generally related to the particles possible inhomogeneous deposition on the surface of the scaffolds, due to its agglomerations, Figure 3 e, formation during the sonication process. To lessen the consequence of serious postoperative infections, systemic and topical antibiotics can be applied postoperatively but that has downsides [ 66 , 67 ]. Systemic administration effects the whole organism but has limited capacity to reach target site.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in the response of the micro TiO 2 based scaffolds, is generally related to the particles possible inhomogeneous deposition on the surface of the scaffolds, due to its agglomerations, Figure 3 e, formation during the sonication process. To lessen the consequence of serious postoperative infections, systemic and topical antibiotics can be applied postoperatively but that has downsides [ 66 , 67 ]. Systemic administration effects the whole organism but has limited capacity to reach target site.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they may possess the potential to restore vision by replacing dead photoreceptors and RPE cells in atrophic AMD and RP, and dying retinal ganglion cells (RGCs) in glaucoma and other ocular nerve atrophies [ 79 ]. Alternatively, there are limitations to the promise of stem cells, and yet there are no FDA-approved stem cell therapies for retinal disease [ 80 ]. Experimental studies have shown that MSCs differentiated into RPE-like cells with similar morphological features that could replace damaged cells when applied to damaged retinas, and this retreatment was well tolerated, with no intraocular inflammation or proliferation [ 81 ].…”
Section: Gene Delivery Carriers To the Retinamentioning
confidence: 99%
“…16 Gel is a readily available and inexpensive natural polymer characterized by low toxicity and inflammatory response. 17 However, there are controversial results on the effect of PCL/Gel blend on different cell types. In some studies, it was reported that PCL blending with Gel may enhance cell adherence.…”
Section: Cell Culturementioning
confidence: 99%